Fostering Digital Agency Through Scaffolding in Social Studies Education: A Systematic Literature Review - Budi Kurnia; Ani Rusilowati; Nina Witasari (Proceedings of International Conference on Science, Education, and Technology, 2026)
Digital transformation shifts the orientation of Social Studies education from content acquisition toward developing students' digital agency for critical participation in society. Although research on digital literacy expands, a comprehensive synthesis regarding the role of scaffolding in fostering digital agency within Social Studies remains limited. This study aims to analyze study characteristics, thematic clusters, intervention impacts, and implementation challenges of scaffolding-based digital agency. Utilizing a Systematic Literature Review (SLR) guided by the PRISMA 2020 statement and rigorous Quality Assessment, 11 core empirical articles from the 2015-2025 period were retrieved from the Scopus database. Qualitative-thematic synthesis crystallizes the literature into five main clusters: digital literacy, civic participation, instructional technology, disciplinary thinking, and teacher professional learning. The implemented scaffolding strategies proved highly effective in enhancing students' cognitive-evaluative capacities, such as data literacy and critical source evaluation. However, their impact on active digital civic engagement outside the classroom remains moderate-to-low. Key challenges identified include the dominance of epistemic control in learning orientations and the fragmentation between techno-pedagogical designs and the core essence of civic education. This study contributes to formulating an integrated conceptual model and mapping critical research gaps to guide future Social Studies instructional designs oriented toward active digital citizenship.